Benefits and risks of antimicrobial use in food-producing animals - Hao, Haihong; Cheng, Guyue; Iqbal, Zahid; Ai, Xiaohui; Hussain, Hafiz I.; Huang, Lingli; Dai, Menghong; Wang, Yulian; Liu, Zhenli; Yuan, Zonghui (Frontiers in Microbiology, 2014)
Benefits and risks of antimicrobial drugs, used in food-producing animals, continue to be complex and controversial issues. This review comprehensively presents the benefits of antimicrobials drugs regarding control of animal diseases, protection of public health, enhancement of animal production, improvement of environment, and effects of the drugs on biogas production and public health associated with antimicrobial resistance. The positive and negative impact, due to ban issue of antimicrobial agents used in food-producing animals, is also included in discussion. As a double-edged sword, use of these drugs in food-animals persists as a great challenge.